Mechanisms of Coronary Artery Spasm - Kensuke Nishimiya; Jun Takahashi; Kazuma Oyama; Yasuharu Matsumoto; Satoshi Yasuda; Hiroaki Shimokawa (European Cardiology Review)
Recent clinical trials have highlighted that percutaneous coronary intervention in patients with stable angina provides limited additional benefits on top of optimal medical therapy. This has led to much more attention being paid to coronary vasomotion abnormalities regardless of obstructive or non-obstructive arterial segments. Coronary vasomotion is regulated by multiple mechanisms that include the endothelium, vascular smooth muscle cells (VSMCs), myocardial metabolic demand, autonomic nervous system and inflammation. Over the years, several animal models have been developed to explore the central mechanism of coronary artery spasm. This review summarises the landmark studies on the mechanisms of coronary vasospasm demonstrating the central role of Rho-kinase as a molecular switch of VSMC hypercontraction and the important role of coronary adventitial inflammation for Rho-kinase upregulation in VSMCs.